Moral hazard in mudarabah financing: Drivers, mitigation strategies, and implications for the welfare of the ummah - Muh. Sajjaj Sudirman; Hasnidar (JIFA (Journal of Islamic Finance and Accounting), 2026)
Mudarabah financing is particularly vulnerable to moral hazard because it relies heavily on trust while separating fund ownership from business management. This study examines the drivers of moral hazard in mudarabah financing and identifies mechanisms through which Islamic financial institutions can mitigate such risks while supporting the broader welfare objectives of Islamic finance. A descriptive qualitative approach was employed through a structured review of 44 relevant sources published between 2014 and 2024, selected using predefined search terms and eligibility criteria. The findings show that moral hazard may arise from both parties to the mudarabah contract: the fund owner (shahibul maal) and the fund manager (mudharib). Its principal drivers include weak monitoring and evaluation, conflicts of interest, information asymmetry, inadequate due diligence, and an understanding of accountability that remains limited to human relationships while overlooking responsibility to God, society, and the natural environment. The review identifies several complementary mitigation mechanisms, including signaling and screening, enhanced transparency and supervision, rigorous due diligence, clear and incentive-compatible contracts, balanced incentives and sanctions, continuous education and training, periodic reporting in accordance with applicable accounting standards, and regular Sharia audits. The study contributes by integrating economic, institutional, and ethical perspectives to explain moral hazard as a two-sided problem in mudarabah financing. The findings provide practical guidance for developing stronger monitoring systems and digital oversight mechanisms, while highlighting the need for more robust governance and supervisory standards. Effective mitigation may ultimately strengthen public trust, broaden financial inclusion, and enhance the contribution of Sharia-compliant financing to the welfare of the ummah.